Understanding Student Digital Burnout through the Perspective of Cognitive Load Theory: A Phenomenological Study on Online Learning Experiences in Higher Education - Barokatus Sholihah; Sri Arini Chudriati; Adzrin Subarna; Abdul Fikri; Yayah Nurhidayah (P3M STAI Kuningan, 2026)
The increasing adoption of online learning in higher education has intensified students' interaction with digital technologies. While this transformation provides greater learning flexibility, it also increases cognitive demands that may contribute to digital burnout. Previous studies have predominantly examined this phenomenon using quantitative approaches, leaving students' lived experiences insufficiently explored. Therefore, this study aims to understand students' experiences of digital burnout in online learning through the perspective of Cognitive Load Theory (CLT). A qualitative approach with an Interpretative Phenomenological Analysis (IPA) design was employed. Ten active students who had experienced intensive online learning and digital fatigue were purposively selected. Data were collected through semi-structured interviews and analyzed using the IPA stages of reading and re-reading, initial noting, emergent themes, theme clustering, and cross-case analysis. The findings revealed five interrelated themes: the complexity of learning materials, the digital burden of the learning environment, the emergence of digital burnout, its academic and psychological consequences, and students' adaptation strategies. Participants described difficulties in understanding learning materials independently, managing multiple digital platforms, and coping with continuous academic information, which gradually led to mental exhaustion, reduced motivation, impaired concentration, procrastination, and emotional distress. From the CLT perspective, these experiences suggest that extraneous cognitive load emerged as the primary source of digital burden, while students adopted time management, digital detox, and social support as adaptive responses. These findings extend qualitative understanding of digital burnout and highlight the importance of designing online learning environments that minimize unnecessary cognitive load while supporting student well-being.